Literasi Olahraga Berbasis Kearifan Lokal: Upaya Kolaboratif Antara Sekolah dan Sekolah Adat Moi, Kabupaten Sorong - Emayanti; Oktrin; Kurniadi, Agus Kurniadi; Robi, La; Istiyono (Jurnal Muara Olahraga, 2025)
literacy through collaboration between formal schools and the Moi Traditional School in Sorong District, Papua Barat Daya, Indonesia. In the context of globalization, preserving indigenous values while promoting health and physical education presents both a challenge and an opportunity. The study aims to describe how the Moi community’s cultural practices—particularly traditional games, movement arts, and local rituals—can be transformed into educational content that supports students' physical literacy, identity, and cultural integrity. Utilizing a qualitative descriptive method, this research finds that the collaborative model fosters not only student engagement in physical activities but also strengthens cultural transmission. Keywords: sports literacy, local wisdom, indigenous peoples' education, Moi tribe, cultural collaboration, physical education